2′-fucosyllactose alone or combined with resistant starch increases circulating short-chain fatty acids in lean men and men with prediabetes and obesity - Canfora, Emanuel E.; Vliex, Lars M. M.; Wang, Taojun; Nauta, Arjen; Bouwman, Freek G.; Holst, Jens J.; Venema, Koen; Zoetendal, Erwin G.; Blaak, Ellen E. (Frontiers in Nutrition, 2023)
Background: Infusion of short-chain fatty acids (SCFA) to the distal colon beneficially affects human substrate and energy metabolism. Here, we hypothesized that the combination of 2’-fucosyllactose (2’-FL) with resistant starch (RS) increases distal colonic SCFA production and improves metabolic parameters. Methods: In this randomized, crossover study, ten lean (BMI 20-24.9kg/m2) and nine men with prediabetes and overweight/obesity (BMI 25-35kg/m2) were supplemented with either 2’-FL, 2’-FL+RS or placebo one day prior to a clinical investigation day (CID). During the CID, blood samples were collected fasted and after intake of a liquid high-fat mixed meal to determine plasma SCFA (primary outcomes). Secondary outcomes were fasting and postprandial plasma insulin, glucose, free fatty acid (FFA), glucagon-like peptide-1 and peptide YY concentrations. In addition, fecal SCFA and microbiota composition, energy expenditure and substrate oxidation (indirect calorimetry) and breath hydrogen excretion were determined. Results: In lean men, supplementation with 2’-FL increased postprandial plasma acetate (P=0.017) and fasting H2 excretion (P=0.041) compared to placebo. Postprandial plasma butyrate concentration increased after 2’-FL and 2’-FL+RS as compared to placebo (P<0.05) in lean and in men with prediabetes and overweight/obesity. Additionally, 2’-FL+RS decreased fasting and postprandial plasma FFA concentrations compared to placebo (P<0.05) in lean men. Conclusion: Supplementation of 2’-FL with/without RS the day prior to investigation increased systemic butyrate in lean men as well as in men with prediabetes and obesity, whilst acetate was only increased in lean men. The combination of 2’-FL with RS showed a putatively beneficial metabolic effect by lowering plasma FFA in lean men, indicating a phenotype-specific effect.